Post a New Question

math

posted by on .

How would you solve for x in this equation:
(x^2-9)(2x-1)=0

  • math - ,

    For the problem, a value of x which makes a factor 0 is a solution.
    (x^2-9)(2x-1) = 0
    factoring (x^2-9) further
    (x+3)(x-3)(2x-1) = 0
    For each factor, what value of x will make the term 0?
    The first term, (x+3), will be 0 for x=-3.
    The second term is 0 for x=?
    The third term is 0 for x=?

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question